"It's a lifeline": Generating a sense of social connectedness through befriending parents of disabled children or children with additional need. Issue 12 (December 2019) - Blake, Lucy; Bray, Lucy; Carter, Bernie
Highlights: Engaging in a befriending scheme had a positive impact on the parents. Parents benefitted from forming social connections within a community of parents. Social connectedness is a useful concept to consider in befriending studies. Abstract: Objectives: This study explored the influence of a parent-to-parent peer support scheme on the wellbeing of parents of disabled children or children with additional need who joined a befriending scheme. Methods: A longitudinal concurrent mixed methods (qualitative and quantitative) research design collected data (telephone interviews, Footsteps Tool, Resilience Scale-14) with 33 befriendees (1:1 or group support) and 33 befrienders at time-point 1 (TP1). TP2 data were collected from 20 befriendees and 16 befrienders 6–9 months after recruitment. Results: There was some improvement on average scores between TP1 and TP2 on both tools. The strongest evidence of change - 'a sense of positivity and hope' and 'connection, belonging and sharing' - was in the parents' reports of how the scheme helped them to build secure and valued social connections within a community of other parents who understood their lives. Conclusion: Both the befriendees and befrienders reported the sense of hope and a feeling of belonging as key benefits that resulted from the social connections they gained from the scheme. Practice implications: Social connectedness is likely to be a more useful concept than resilience in examining change.